Where does the chilean aconcagua river come from? Use of natural tracers for water genesis characterization in glacial and periglacial environments - Crespo, Sebastián Andrés (2020)
The Aconcagua river basin (Chile, 32◦S) has suffered the effects of the megadrought over the last decade. The severe snowfall deficiency drastically modified the water supply to the catchment headwaters. Despite the recognized snowmelt contribution to the basin, an unknown streamflow buffering effect is produced by glacial, periglacial and groundwater inputs, especially in dry periods. Hence, each type of water source was characterized and quantified for each season, through the combination of stable isotope and ionic analyses as natural water tracers. The δ18O and electric conductivity were identified as the key parameters for the differentiation of each water source. The use of these parameters in the stable isotope mixing “simmr” model revealed that snowmelt input accounted 52% in spring and only 22–36% during the rest of the year in the headwaters. While glacial supply contributed up to 34%, both groundwater and periglacial exhibited a remarkable contribution around 20% with some seasonal variations. Downstream, glacial contribution averaged 15–20%, groundwater seasonally increased up to 46%, and periglacial input was surprisingly high (i.e., 14–21%). The different water sources contribution quantification over time for the Aconcagua River reported in this work provides key information for water security in this territory.